2018
DOI: 10.1017/s1751731117001811
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences of semen quality, seminal plasma, and spermatozoa antioxidative and oxidative stress variables in bulls during cold and warm periods of the year

Abstract: The aims of this study were to determine the presence and quantities of antioxidative status and oxidative stress (OS) variables in the seminal plasma and spermatozoa of bulls of varying age during cold and warm periods of the year, and to establish the correlation of these variables with semen quality parameters. The study was conducted on two groups each comprising nine Simmental bulls: one group contained younger animals (aged 2 to 4 years) and the second older animals (aged 5 to 10 years). Semen samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 30 publications
(45 reference statements)
1
16
0
3
Order By: Relevance
“…The average activities of SOD signifi cantly differed between groups in S1-5, but not afterwards, which can be explained by high SOD consumption in the neutralisation of free radicals resulting from long-lasting heat stress. This fi nding is in compliance with the results published by Vince et al [42], who detected high activities of SOD in Simmental bulls in summer. Nichi et al [16] proved in bulls of the same breed a higher degree of lipid peroxidation in the semen in the summer period, which means that the organism by means of its antioxidative enzyme system tends to resist to the process and thus prevent the production of semen of lower quality.…”
Section: Discussionsupporting
confidence: 93%
“…The average activities of SOD signifi cantly differed between groups in S1-5, but not afterwards, which can be explained by high SOD consumption in the neutralisation of free radicals resulting from long-lasting heat stress. This fi nding is in compliance with the results published by Vince et al [42], who detected high activities of SOD in Simmental bulls in summer. Nichi et al [16] proved in bulls of the same breed a higher degree of lipid peroxidation in the semen in the summer period, which means that the organism by means of its antioxidative enzyme system tends to resist to the process and thus prevent the production of semen of lower quality.…”
Section: Discussionsupporting
confidence: 93%
“…Vince e colaboradores (17) vão mais além e apontam que fatores intrínsecos como o ambiente, a raça e a idade podem alterar de forma significativa parâmetros andrológicos, como motilidade e concentração espermática. O que corrobora os relatos de Thundathil et al (18) , em que a taxa de fertilidade pode variar em até 20% entre touros classificados como excelentes reprodutores, pois há alterações nos aspectos microscópicos do sêmen.…”
Section: Resultsunclassified
“…A correlação baixa encontrada entre motilidade e defeitos totais define-se por serem variáveis dependentes. A literatura registra que uma alteração na espermatogênese, como um aumento da temperatura ambiente ou corpórea, promove de forma significativa uma alteração na qualidade morfológica das células espermáticas, com interferência na produção e na viabilidade do espermatozoide (17).…”
Section: Resultsunclassified
“…For example, a study on cockerels showed that the concentration of uric acid in seminal plasma may be affected by the semen collection method [ 9 ]. In addition, the mean value of seminal urate was found to be higher in younger bulls compared to old ones [ 10 ]. Moreover, uric acid in semen was found to be affected by temperature; its level was found to be higher in cold conditions compared to warm conditions [ 10 ].…”
Section: Uric Acid As a Component Of Semenmentioning
confidence: 99%
“…In addition, the mean value of seminal urate was found to be higher in younger bulls compared to old ones [ 10 ]. Moreover, uric acid in semen was found to be affected by temperature; its level was found to be higher in cold conditions compared to warm conditions [ 10 ].…”
Section: Uric Acid As a Component Of Semenmentioning
confidence: 99%